1991
DOI: 10.1128/jvi.65.2.992-995.1991
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine enhances replication of Semliki Forest virus and encephalomyocarditis virus in mice

Abstract: Chloroquine (CHL) has been suggested to play an important role in the development of Burkitt's lymphoma by enhancing Epstein-Barr virus expression. Herpes zoster virus incidence is markedly increased following malaria infection in children being treated with CHL. Recently, CHL has also been shown to dramatically increase the transactivation of Tat protein purified from human immunodeficiency virus. These previous studies indirectly suggest that CHL may be involved in the enhancement of virus replication. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 17 publications
1
30
0
2
Order By: Relevance
“…The potential for in cellulo application of chloroquine as an antiviral treatment was first reported more than 40 years ago (Inglot, 1969), but in the case of alphaviruses, and notably SFV, it was also reported that chloroquine enhanced virus replication in mice (Maheshwari et al, 1991). In vitro inhibition of CHIKV replication by chloroquine has been reported (Delogu and de Lamballerie, 2011) and should be distinguished from the anti-inflammatory effect previously reported in patients at the chronic stage of infection (Brighton, 1984).…”
Section: Interferonmentioning
confidence: 98%
“…The potential for in cellulo application of chloroquine as an antiviral treatment was first reported more than 40 years ago (Inglot, 1969), but in the case of alphaviruses, and notably SFV, it was also reported that chloroquine enhanced virus replication in mice (Maheshwari et al, 1991). In vitro inhibition of CHIKV replication by chloroquine has been reported (Delogu and de Lamballerie, 2011) and should be distinguished from the anti-inflammatory effect previously reported in patients at the chronic stage of infection (Brighton, 1984).…”
Section: Interferonmentioning
confidence: 98%
“…The case of chikungunya virus (CHIKV) is of specific interest: chloroquine showed promising antiviral activity in vitro (Coombs et al, 1981;Delogu and de Lamballerie, 2011), but was shown to enhance alphavirus replication in various animal models (Maheshwari et al, 1991;Roques et al, 2018;Seth et al, 1999), most probably because of the immune modulation and anti-inflammatory properties of chloroquine in vivo (Connolly et al, 1988;Katz and Russell, 2011;Savarino et al, 2003). In a nonhuman primate model of CHIKV infection, chloroquine treatment was shown to exacerbate acute fever and delay the cellular immune response, leading to an incomplete viral clearance (Roques et al, 2018).…”
mentioning
confidence: 99%
“…However, in-vivo, CHL/HCHL have been shown to either have no effect on virus replication or have increased the viral replication and disease severity such as that of influenza [7], dengue [8,9], Semliki forest virus (SFV) [10,11], encephalomyocarditis virus (EMCV) [10], Nipah and Hendra viruses [12], chikungunya virus [13] and Ebola virus [14]. In clinical trials, CHL treatment failed to prevent influenza and chikungunya virus infections in human subjects and was suggested to increase the risk of infection as well as symptom severity [7,15].…”
Section: Main Textmentioning
confidence: 99%
“…Although encouraging, the difference of treating inflammation of COVID-19 vs SLE or RA is the presence of an infectious agent i.e., SARS-CoV-2. In animal studies, CHL enhanced severity of the inflammatory viral disease such as that of SFV and EMCV, and increased arthritic symptoms in CHIKV infected patients [10,25]. Therefore, beneficial anti-inflammatory effect of CHL may not translate as it is, into SARS-CoV-2 infected patients.…”
Section: Main Textmentioning
confidence: 99%